Developing speed strength: In-season training program for the collegiate thrower - Judge, L. C. (Strength and Conditioning Journal, 2007)
Specificity is a vital concept in track and field training for the throwing events. Specific physiological/ performance characteristics can be developed by emphasizing specific training variables. Exercises must be specifically designed for the demands of the event. Effective program design must address energetics, mechanics, and coordination characteristics specific to throwing. The goal of final preparation in the competition phase is to develop speed strength and to maximize fitness, to fine-tune skills but minimize fatigue on the day of the competition.